High Liquidity Creation and Bank Failures : Do They Behave Differently? - Fungacova, Zuzana (IMF Working Papers; Working Paper ;, 2015)
We formulate the 'High Liquidity Creation Hypothesis' (HLCH) that a proliferation in the core activity of bank liquidity creation increases failure probability. We test the HLCH in the context of Russian banking, which provides a natural field experiment due to numerous failures experienced over the past decade. Using Berger and Bouwman's (2009) liquidity creation measures as a comprehensive proxy for overall bank output, we find that high liquidity creation significantly increases the probability of bank failure; this finding survives multiple robustness checks. Our results suggest that regulatory authorities can mitigate systemic distress and reduce the costs of bank failures to society through early identification of high liquidity creators and enhanced monitoring of their funding and investment activities.